Heart rate recovery: autonomic determinants, methods of assessment and association with mortality and cardiovascular diseases - Peçanha, Tiago; Silva-Júnior, Natan Daniel; Forjaz, Cláudia Lúcia de Moraes (Clinical physiology and functional imaging, 2014)
Summary Cardiovascular disease (CVD) is the primary cause of mortality worldwide. Cardiac autonomic dysfunction seems to be related to the genesis of several CVDs and is also linked to the increased risk of mortality in CVD patients. The quantification of heart rate decrement after exercise – known as heart rate recovery (HRR) – is a simple tool for assessing cardiac autonomic activity in healthy and CVD patients. Furthermore, since The Cleveland Clinic studies, HRR has also been used as a powerful index for predicting mortality. For these reasons, in recent years, the scientific community has been interested in proposing methods and protocols to investigate HRR and understand its underlying mechanisms. The aim of this review is to discuss current knowledge about HRR, including its potential primary and secondary physiological determinants, as well as its role in predicting mortality. Published data show that HRR can be modelled by an exponential curve, with a fast and a slow decay component. HRR may be influenced by population and exercise characteristics. The fast component mainly seems to be dictated by the cardiac parasympathetic reactivation, probably promoted by the deactivation of central command and mechanoreflex inputs immediately after exercise cessation. On the other hand, the slow phase of HRR may be determined by cardiac sympathetic withdrawal, possibly via the deactivation of metaboreflex and thermoregulatory mechanisms. All these pathways seem to be impaired in CVD, helping to explain the slower HRR in such patients and the increased rate of mortality in individuals who present a slower HRR.